Trade-off between risk and returns in farmers’ choice of crops? Evidence from India - Pratap S Birthal; Digvijay S Negi; Jaweriah Hazrana (Agricultural Economics Research Review, 2023)
This paper has assessed variation in the exposure and vulnerability of crops to production risks such as droughts, floods and pests; and subsequently the trade-off between risk and returns in farmers’ choice of crops. Findings show that, at any point of time, about one-third of the farm households are exposed to production risks and suffer a loss of about 12% in their potential farm returns. Drought accounts for about 47% of the total loss, followed by insect-pests (27%) and floods (20%). There is a considerable variation in exposure and vulnerability of crops to drought risk, but not much to flood and pest risks. The low-risk crops, mainly staple cereals, generate less but stable returns, and the crops that are more remunerative to produce are also more vulnerable to risks. In general, we find that risk-averse farmers choose low-return, low-risk crop portfolio, but those capable of bearing the cost of risks prefer a high-return, high-risk crop portfolio.